Flame retardance of epoxy acrylate resin modified with phosphorus containing compounds - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (ELSEVIER SCIENCE SA, 2004)
In this work, UV radiation curing of allyldiphenyl phosphine oxide (ADPPO) and 4,4'-bis(allyloxyphenyl) phenyl phosphine oxide (DAPPO) monomers with epoxy acrylate resin in the presence of a photoinitiator was studied and their flame-retardant performance compared with pure epoxy acrylate film. The structures of allyl functional phosphorus compounds were characterized by FT-IR, H-1 NMR, C-13 NMR and all spectra were consistent with the expected structures. The polymerization behavior of both allyl functional monomers was followed in detail by monitoring the disappearance of acrylate and allyl groups by real-time infrared spectroscopy. It was obtained that the reactivity of DAPPO monomer is higher than ADPPO. In the case of ADPPO, chain transfer to monomer basically predominates. In each monomer, a tack free coating was obtained immediately upon irradiation. The addition of DAPPO leads to an improvement of the thermal and flame-retardant properties of the polymeric films. Thermal gravimetric analysis of DAPPO containing polymeric films gave higher char yield compared with UV cured pure epoxy acrylate resin. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: UV-curing; phosphorus; flame retardance; allylic oligomers; kinetics; POLYMERIZATION; KINETICS; OXIDE